Efforts to Improve Learning Outcomes of Badminton Long Service Using Student's Reciprocal Teaching Style Class XI SMAN 1 Bagan Sinembah: Upaya Meningkatkan Hasil Belajar Service Panjang Bulutangkis Dengan Menggunakan Gaya Mengajar Resiprokal Siswa Kelas XI SMAN 1 Bagan Sinembah - Eris Wijaya Pohan; Mimi Yulianti (Badnur Medisa Group, 2022)
The purpose of this study was to find out the efforts to improve the long serve learning outcomes of badminton with the reciprocal teaching style of class XI students of Senior High School 1 Bagan Sinembah. This type of research is PTK (Classroom Action Research). The subjects of this study were students of class XI at Senior High School 1 Bagan Sinembah which consisted of 1 class consisting of 36 students, 16 boys and 20 girls. The instrument used in this research is performance research. This study resulted in an increase in student data on badminton long serve learning to use a reciprocal teaching style. Mastery student learning outcomes in the first cycle of 25.00%, and in cycle II of 96.00%. The conclusions that can be drawn in this study are: the use of the reciprocal method can improve the learning outcomes of long serve badminton for class XI students of Senior High School 1 Bagan Sinembah.